Diagnostic Performance of PET or PET/CT with Different Radiotracers in Patients with Suspicious Lung Cancer or Pleural Tumours according to Published Meta-Analyses. (25th April 2020) - Lococo, Filippo; Muoio, Barbara; Chiappetta, Marco; Nachira, Dania; Petracca Ciavarella, Leonardo; Margaritora, Stefano; Treglia, Giorgio
Abstract : Purpose . Several meta-analyses have reported data about the diagnostic performance of positron emission tomography or positron emission tomography/computed tomography (PET or PET/CT) with different radiotracers in patients with suspicious lung cancer (LC) or pleural tumours (PT). This review article aims at providing an overview on the recent evidence-based data in this setting. Methods . A comprehensive literature search of meta-analyses published in PubMed/MEDLINE and Cochrane Library database from January 2010 through March 2020 about the diagnostic performance of PET or PET/CT with different radiotracers in patients with suspicious LC or PT was performed. This combination of keywords was used: (A) "PET" OR "positron emission tomography" AND (B) "lung" OR "pulmonary" OR "pleur ∗ " AND (C) meta-analysis. Only meta-analyses on PET or PET/CT in patients with suspicious LC or PT were selected. Results . We have summarized the diagnostic performance of PET or PET/CT with fluorine-18 fluorodeoxyglucose ( 18 F-FDG) and other radiotracers taking into account 17 meta-analyses. Evidence-based data demonstrated a good diagnostic performance of 18 F-FDG PET or PET/CT for the characterization of solitary pulmonary nodules (SPNs) or pleural lesions with overall higher sensitivity than specificity. Evidence-based data do not support the routine use of dual time point (DTP) 18 F-FDG PET/CT or fluorine-18 fluorothymidine ( 18 F-FLT) PET/CT in the differential diagnosis of SPNs. Even if 18 F-FDG PET/CT has high sensitivity and specificity as a selective screening modality for LC, its role in this setting remains unknown. Conclusions . Evidence-based data about the diagnostic performance of PET/CT with different radiotracers for suspicious LC or PT are increasing, with good diagnostic performance of 18 F-FDG PET/CT. More prospective multicenter studies and cost-effectiveness analyses are warranted.